STRATEGI OPTIMASI MENGGUNAKAN METODE GAME THEORY DAN MARKOV CHAIN TERHADAP LAYANAN MARKETPLACE - Hasugian, Abdul Halim; Fakhriza, M.; Lubis, Desy Ramadhani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Technological developments in the current era of globalization cannot be denied, especially in the business and social fields, technological developments provide enormous benefits and make it easier for people to carry out business transactions and communicate. Technology also plays a role in improving the quality of the community's economy. Competition in the modern world, especially in the digital world, is increasing with its use in community activities, one of which is the marketplace. Its use is quite easy and efficient, causing many people to be interested in it. This research aims to analyze optimal marketplace competition strategies using Game Theory and Markov Chain methods. Game Theory is a theory in operations research that discusses marketing or competition problems for a company or object being studied. In solving Game Theory using pure strategy and mixed strategy. Apart from determining the optimal strategy in competition, it is also necessary to look at market conditions regarding consumer movements in using marketplaces with Markov chains. Markov chain is a method used to predict the market share of a product in the current period as a basis for predicting future market share. The research results obtained show that Shopee produces optimal strategies, namely security and vouchers and cashback, while Tokopedia produces optimal strategies, namely price, security and promotions. Brand switching using Markov Chain produces a probability for Shopee of 0.431 and Tokopedia of 0.569. Keywords: game theory, markov chain, marketplace, competition, optimal strategy, brand switching Abstrak: Perkembangan teknologi di era globalisasi seperti saat ini tidak dapat dipungkiri lagi terutama dibidang bisnis maupun sosial, perkembangan teknologi memberikan manfaat yang begitu besar dan lebih memudahkan masyarakat dalam melakukan transaksi bisnis dan berkomunikasi. Tekonologi juga berperan dalam peningkatan mutu perekonomian masyarakat. Persaingan di dunia modern terutama dalam dunia digital semakin meningkat dengan pemanfaatannya dalam kegiatan masyarakat salah satunya adalah marketplace. Penggunaannya yang cukup mudah dan efisien menyebabkan banyak masyarakat meminatinya. Penelitian ini bertujuan untuk menganalisis strategi persaingan marketplace yang optimal menggunakan metode Teori Permainan dan Rantai Markov. Dalam penyelesaian Game Theory menggunakan strategi murni dan strategi campuran. Selain menentukan strategi optimal dalam persaingan, dibutuhkan juga untuk melihat kondisi pasar tentang perpindahan konsumen dalam menggunakan marketplace dengan markov chain. Markov chain merupakan salah satu metode yang digunakan untuk memprediksi pangsa pasar suatu produk pada periode saat ini sebagai dasar untuk memprediksi pangsa pasar yang akan datang. Hasil penelitian yang diperoleh menunjukkan bahwa pada Shopee menghasilkan strategi optimal yaitu keamanan dan voucher dan cashback, sedangkan pada Tokopedia menghasilkan strategi optimal yaitu harga, keamanan, dan promosi. Perpindahan merek menggunakan Markov Chain menghasilkan probabilitas Shopee 0,431 dan Tokopedia 0,569.Kata kunci: teori permainan, rantai markov, marketplace, persaingan, strategi   optimal, perpindahan merek